Biological control of earhead caterpillar, Helicoverpea armigera Hubner in sorghum (The Journal of Plant Protection Sciences, 2020)
A field experiment was conducted with biopesticides viz., Nomurae rileyi (Farlow) Samson and NPV of Helicoverpa armigera (HNPV) and compared with chemical control with Melathian 5% @ 30 kg.ha-1 for the management of ear head caterpillar (H. armigera) in sorghum ecosystem of University of Agricultural Sciences, Dharwad. The mycoinsecticide N. rileyi was highly infective at both the dosages 1x108 conidia per litre & 2x108 conidia per litre against H. armigera as compared to Ha NPV 250 LE per hectare and chemical control in mitigating the pest population as well as in obtaining the higher yield.
Keywords: Helicoverpa armigera; Nomuraea rileyi; sorghum; biopesticides